2003
DOI: 10.1892/0891-6640(2003)017<0908:tcnosi>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Neurology of Scrapie in Irish Sheep

Abstract: One hundred twenty-nine sheep with scrapie were identified from 20 flocks in which scrapie previously had been confirmed. Physical and neurologic examinations were performed on all animals. Videotape recordings were made and reviewed to assess gait. These procedures were repeated in 46 sheep at 2-to 3-week intervals until recumbency or inappetence necessitated euthanasia. Confirmation of scrapie was made by histopathologic and immunohistochemical examinations of brain tissue. The clinical signs most frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Pruritus is a clinical sign usually associated with classical scrapie but its occurrence can vary significantly. In a recent study in Ireland, only 25% of 129 examined sheep displayed pruritus [2] whilst other studies in Italy and the UK reported pruritus in approximately 85% of 550 sheep [1] and 86% of 35 sheep [17] respectively. Ataxia was observed in 79.5% of 116 scrapie-affected sheep in Ireland and in 80% of sheep in the Italian study [1], whilst it was seen in all 35 sheep in the UK [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pruritus is a clinical sign usually associated with classical scrapie but its occurrence can vary significantly. In a recent study in Ireland, only 25% of 129 examined sheep displayed pruritus [2] whilst other studies in Italy and the UK reported pruritus in approximately 85% of 550 sheep [1] and 86% of 35 sheep [17] respectively. Ataxia was observed in 79.5% of 116 scrapie-affected sheep in Ireland and in 80% of sheep in the Italian study [1], whilst it was seen in all 35 sheep in the UK [17].…”
Section: Discussionmentioning
confidence: 99%
“…Ataxia was observed in 79.5% of 116 scrapie-affected sheep in Ireland and in 80% of sheep in the Italian study [1], whilst it was seen in all 35 sheep in the UK [17]. The reason for this variation is poorly understood but it may be the effect of genotype [2], breed or strain, which are thought to be the cause for the variation in the neuropathology in classical scrapie [18-20]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paresis and ataxia, especially of the hindlimbs, are common clinical signs (Healy andothers 2003, Jeffrey andGonzalez 2007); quadriplegia and recumbency are seen at a later date. Other clinical signs include separation from the rest of the flock, depression, anxiety or hyperexcitability, head tremor, low head carriage, pruritus (including a 'nibble' response to stimulation of the back), weight loss, bruxism, cud-dropping and an absent menace response (Healy andothers 2003, Konold andPhelan 2014). Most of the sheep that are affected are more than two years of age (Jeffrey and Gonzalez 2007).…”
Section: Scrapiementioning
confidence: 99%